FUNCTIONAL PROFILE AND ASSOCIATED IMPAIRMENTS IN SCHOOL-AGED CHILDREN WITH CEREBRAL PALSY IN SERBIA - Milićević, Milena (HEALTH CARE, 2025)
Introduction/Aim: Cerebral palsy is a permanent and heterogeneous condition that requires continuous, comprehensive support from multiple service providers, including healthcare professionals. Information on functional characteristics of individuals with cerebral palsy is necessary for effective service planning and counselling families in a clinical context. However, no national database or register is available in Serbia. This descriptive and exploratory study aimed to examine functional characteristics and frequency of associated impairments in a sample of school-aged children with cerebral palsy in Serbia. Methods: A convenience sample of 117 children and adolescents with cerebral palsy (56.4% male), aged 7–18 years (M = 13.23, SD = 3.36), was analysed. Data on cerebral palsy type, gross motor function, fine manual and bimanual abilities, intellectual functioning, sensory impairments (visual, hearing), epilepsy, and general health problems were extracted from available medical, educational, and psychological records. Descriptive statistics were used for analysis.Results: Spastic cerebral palsy was the most common type (65.8%), frequently accompanied by intellectual disability (67.5%), visual impairment (33.3%), and epilepsy (24.7%). Nearly two-thirds (64.1%) of participants had two or more associated impairments. The majority exhibited limitations in ambulation, manual performance, and fine motor skills.Conclusion: The basic functional characteristics and frequency of associated impairments were generally in line with national and international reports, with some differences observed in comorbidity patterns. The high prevalence of multiple health and developmental challenges underscores the urgent need for a national cerebral palsy registry in Serbia.
Keywords: spastic cerebral palsy, infantile cerebral palsy, comorbidity, functional profile